Supporting early language development : spirals for babies and toddlers - Nash, Marion; Lowe, Jackie; Leah, David (New York, NY : Routledge, 2012)
'Research shows that poor language and communication skills have a profound effect on the life chances of children and young people. This highly practical book will enable you to give children in your care the help they need to build their language skills at the earliest point in their development. Based on the author's highly regarded SPIRALS language development programme, the book provides 40 tried and tested sessions to help develop children's early speech, language and communication. Each language concept is introduced one at a time and builds on the most frequently used words by infants and uses music, repetition and simple meaningful gestures and signing to reinforce children's understanding. Features include: - Concise explanations of the terms and concepts involved - Clear guidelines for setting up and running individual and group sessions - Ideas for progression - Suggestions for involving parents - Photocopiable resources - Lists of further reading and resources Written by a leading authority in the field, this exciting new resource provides everything you need to support young children's language skills at the earliest point in their development'--
Includes index.
Keywords: Children -- Language; Language arts (Early childhood).